2017
DOI: 10.1016/j.bbmt.2017.03.002
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Splenectomy in Myelofibrosis Patients before Allogeneic Hematopoietic Stem Cell Transplantation

Abstract: Performing a pretransplantation splenectomy in patients with myelofibrosis (MF) is a matter of debate, as while the procedure improves hematological recovery, it may lead to severe morbidities. We retrospectively analyzed data from 85 consecutive patients who underwent transplantation in our center for MF, including 39 patients who underwent splenectomy before their transplantation. A majority of them had primary MF (78%), were considered high-risk patients (84% dynamic international prognostic scoring system … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
49
0
6

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 64 publications
(56 citation statements)
references
References 17 publications
1
49
0
6
Order By: Relevance
“…18,19,26 Measures to reduce spleen size such splenectomy and splenic irradiation have been employed prior to ASCT to reduce its negative effect on ASCT outcome. [27][28][29] However, splenectomy is generally not preferred due to its perioperative complication risk (infection, thrombosis, bleeding) including a 5 to 10 percent mortality rate. 14,30 Akpek et al reviewed the effect of spleen size in early outcomes of stem cell transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…18,19,26 Measures to reduce spleen size such splenectomy and splenic irradiation have been employed prior to ASCT to reduce its negative effect on ASCT outcome. [27][28][29] However, splenectomy is generally not preferred due to its perioperative complication risk (infection, thrombosis, bleeding) including a 5 to 10 percent mortality rate. 14,30 Akpek et al reviewed the effect of spleen size in early outcomes of stem cell transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…Splenectomy is also sometimes considered as a preparative measure before ASCT, to improve post‐transplant recovery of counts. Published reports in this regard have not been definitive, regarding the advisability of such practice, but agree on its value in terms of faster platelet and granulocyte recovery; these studies have also indicated the lack of detrimental effect on the risk of disease relapse or nonrelapse mortality and morbidity. What is not currently clear is whether or not pretransplant splenectomy in MF results in superior or inferior post‐transplant survival.…”
Section: Discussionmentioning
confidence: 98%
“…The molecular and cytogenetic profile at diagnosis should be considered in order to better determine the optimal timing for transplant and post-transplant outcome. [32][33][34][35][36][37][38][39][40][41][42][43][44][45][46] MIPSS70+ v2.0 should be assessed prior to allo-HSCT because it has been found to be predictive for long-term survival in MF patients after allo-HSCT. 32 In conclusion, the use of RIC allo-HSCT combined with ATG and PTCy results in promising 1-year OS and RFS in patients with MF mainly using MRD and 10/10 MUD grafts.…”
Section: Discussionmentioning
confidence: 99%